Probiomimetics—Novel Lactobacillus-Mimicking Microparticles Show Anti-Inflammatory and Barrier-Protecting Effects in Gastrointestinal Models - Kuhn, Thomas; Koch, Marcus; Fuhrmann, Gregor (Small, 2020)
There is a lack of efficient therapies to treat increasingly prevalent autoimmune diseases, such as inflammatory bowel disease and celiac disease. Membrane vesicles (MVs) isolated from probiotic bacteria have shown tremendous potential for treating intestinal inflammatory diseases. However, possible dilution effects and rapid elimination in the gastrointestinal tract may impair their application. A cell-free and anti-inflammatory therapeutic system—probiomimetics—based on MVs of probiotic bacteria (Lactobacillus casei and Lactobacillus plantarum) coupled to the surface of microparticles is developed. The MVs are isolated and characterized for size and protein content. MV morphology is determined using cryoelectron microscopy and is reported for the first time in this study. MVs are nontoxic against macrophage-like dTHP-1 and enterocyte-like Caco-2 cell lines. Subsequently, the MVs are coupled onto the surface of microparticles according to facile aldehyde-group functionalization to obtain probiomimetics. A significant reduction in proinflammatory TNF-α level (by 86%) is observed with probiomimetics but not with native MVs. Moreover, it is demonstrated that probiomimetics have the ability to ameliorate inflammation-induced loss of intestinal barrier function, indicating their potential for further development into an anti-inflammatory formulation. These engineered simple probiomimetics that elicit striking anti-inflammatory effects are a key step toward therapeutic MV translation.
CRIS-Team Scopus Importer:2021-06-29
Keywords: anti-inflammatory therapy; bacteriomimetics; biomimetics; inflammatory bowel diseases